Professores experientes de uma escola freinetiana: identidade, saberes e processos de aprendizagem - Nascimento, Lenita Martins do (2021)
Considering the relationship, as a teacher and researcher, with aspects related to teacher education and Freinet Pedagogy, this research aims to understand the knowledge, the teaching learning processes and the constitution of the teaching identity, highlighted in the narratives of experienced and active teacher in Freinet Pedagogy. As specific objectives, it seeks to identify the source of learning indicated by these teachers and describe the ways in which knowledge is acquired. The theoretical framework is based on theaching knowledge in the perspective of Tardif (2000, 2012), the learning processes and constitution of the teaching identity and the Freinet Pedagogy itself. With a qualitative approach, with an exploratory and descriptive character, the research had data collected through semi-structured interviews, considering the narratives of the participants. Three experienced teachers, with over 30 years of experience at the same school, were selected. Among the main results, it was possible to discuss knowledge from different sources, especially those related to experience in the profession, and to identify the phases of the teaching career. It was possible to evidence that investigated teachers point as positive the relationship between beginning and experienced teachers for the construction of professional identity, reflection, working in partnership with peers and the formation of a group identify, as a cooperative based in the Modern School Movement and Freinet Pedagogy, and also in the possible dimensions of a Community of Practice of Teacher for professional learning. The school demonstrated to be a place for learning for its teachers, facilitating the professional development. It hoped that such a study can contribute to the recognition of the relevant and pedagogical information, whether for beginning teachers, aspiring teachers to Freinet Pedagogy, or even teachers in their educational practices.